1997
DOI: 10.1164/ajrccm.155.2.9032208
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of lung volume in spontaneously breathing preterm infants.

Abstract: To study the effects of apneic pauses, sighs, and breathing patterns on functional residual capacity (FRC), we measured FRC repeatedly in 48 healthy preterm infants (weight at study 2,042 +/- 316 g [mean +/- SD], postconceptional age 36.6 +/- 2.0 wk), during unsedated sleep using a modified heliox/nitrogen washout technique. Breathing movements and pulse oximeter saturation (SpO2) were recorded throughout and recordings analyzed for the presence of regular and nonregular breathing pattern, apneic pauses, sighs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 22 publications
6
65
0
3
Order By: Relevance
“…Poets et al 10 showed that lung volumes are low during PB in spontaneously breathing preterm infants. These findings of decreased mixed venous pO 2 and lung volumes may explain the relationship between PB and episodes of oxygen desaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Poets et al 10 showed that lung volumes are low during PB in spontaneously breathing preterm infants. These findings of decreased mixed venous pO 2 and lung volumes may explain the relationship between PB and episodes of oxygen desaturation.…”
Section: Discussionmentioning
confidence: 99%
“…23 It has been speculated that PSV may better enable a ventilated neonate to establish a breathing pattern that includes sighs. 24 PSV may be particularly useful in patients who are difficult to manage with a fixed inspiratory time and respiratory rate (eg, PC-CMV).…”
Section: Pressure Support Ventilationmentioning
confidence: 99%
“…14,17,22 Others have demonstrated that a properly inflated lung is important in achieving and maintaining proper oxygenation and that infants with inadequate FRC are more prone to desaturation events. [10][11][12][13] Deckardt et al continuously measured SpO 2 of newborns and delivered continuous positive airway pressure to those who failed to achieve an SpO 2 of 80% by 5 min of age. 4 They found that the use of continuous positive airway pressure improved oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 For infants requiring resuscitation, the mode of oxygen (O 2 ) delivery may be an important factor in affecting oxygenation. [10][11][12][13] Oxygenation is promoted by providing supplemental O 2 and/or establishing functional residual capacity (FRC) using positive pressure. Continuous positive airway pressure is effective at establishing FRC in the newborn and reducing ventilationperfusion mismatch through recruiting collapsed alveoli and stabilizing alveoli that are already patent, thereby improving oxygenation.…”
Section: Introductionmentioning
confidence: 99%